Reduced glucose tolerance and skeletal muscle GLUT4 and IRS1 content in cyclists habituated to a long-term low-carbohydrate, high-fat diet - Webster, C. C.; van Boom, K. M.; Armino, N.; Larmuth, K.; Noakes, T. D.; Smith, J. A.; Kohn, T. A. (International Journal of Sport Nutrition and Exercise Metabolism, 2020)
There is growing interest in low-carbohydrate, high-fat (LCHF) diets (~50 g/day of carbohydrate) for their potential to improve insulin resistance and type 2 diabetes (T2D) (Bueno et al., 2013; Feinman et al., 2015; Hallberg et al., 2019). Within athletic populations, an increasing number of individuals are experimenting with LCHF diets because of body composition and/or to improve fat oxidation (Gregory et al., 2017; Michalczyk et al., 2018; Volek et al., 2016; Webster et al., 2016). However, LCHF diets are partly controversial because many commonly eaten LCHF foods have been implicated in heart disease, obesity, and T2D (Ludwig et al., 2018). A few days of consuming the LCHF diet can increase postprandial blood glucose concentrations in healthy individuals and reduce the capacity of skeletal muscle to oxidize a carbohydrate load, suggesting a typical state of poor glucose clearance rates synonymous with tissue insulin resistance (Bisschop et al., 2001; Himsworth, 1934, 1940; Numao et al., 2012). Although Himsworth (1934) showed that the LCHF diet causes reduced blood glucose clearance in healthy untrained men, the molecular mechanisms have yet to be established.